2016
DOI: 10.1007/s00330-016-4458-4
|View full text |Cite
|
Sign up to set email alerts
|

CT spectral imaging for monitoring the therapeutic efficacy of VEGF receptor kinase inhibitor AG-013736 in rabbit VX2 liver tumours

Abstract: • AG-013736 treatment response was evaluated by CT in a rabbit tumour model. • CT spectral imaging allows for the early treatment monitoring of targeted anti-tumour therapies. • Spectral CT findings correlated with vascular changes after anti-tumour therapies. • Spectral CT is a promising method for assessing clinical treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…Compared with traditional mixed-energy CT, spectral CT has diverse imaging parameters, including base material and single-energy CT imaging. Previous studies showed that the IoD can reflect the tumor microvessel density [ 22 , 33 ]. Tumor microvessels lack the normal vascular wall composition, resulting in retention or extravasation of iodine in the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional mixed-energy CT, spectral CT has diverse imaging parameters, including base material and single-energy CT imaging. Previous studies showed that the IoD can reflect the tumor microvessel density [ 22 , 33 ]. Tumor microvessels lack the normal vascular wall composition, resulting in retention or extravasation of iodine in the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the iodine images were standardized to decrease the individual circulation variation resulting from technical reasons and patients, helping to reconstruct uniform iodine-uptake images and normalize variable gray levels. Previous studies reported the standardization of iodine concentration was beneficial to staging tumors and evaluating treatment response (47)(48)(49). Unlike standardizing iodine uptake by comparing the concentration between tumors and aorta, we compared the iodine concentration between background tissues to the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…is special effector mechanism of VDAs has led to the development of multiparameter imaging biomarkers to monitor early hemodynamic changes, cellular dysfunction, and metabolic disorders before tumor size changes can be detected, including computed tomography (CT), ultrasonography, dynamic contrast-enhanced magnetic resonance (MR) imaging, and diffusion-weighted (DW) MR imaging [8][9][10][11]. Among these imaging biomarkers, MR imaging is currently the most commonly used noninvasive method for evaluating the response of malignant tumors to treatments; a complete set of MRI-derived parameters has been used as morphological, physiological, and metabolic/molecular biomarkers for the detection and characterization of malignant tumors and evaluation of therapeutic treatment effects [4,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%